DARI SKOR KE KUALITAS SOAL: ANALISIS BUTIR TES BERBASIS ANATES DALAM MENGUNGKAP MUTU EVALUASI PEMBELAJARAN DI PONDOK PESANTREN NURUL-HUDA PANDANSARI - Nailil Izza; Mifta Ayu Fadillah; Rahma Aulia Zahra; Niswah Atqiya Maulidya; M. Wildan Ahfadh (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the quality of multiple-choice test items based on the Anates application in the evaluation of learning at the PDF Nurul Huda Pandansari Islamic Boarding School. This study employed a quantitative descriptive method with 20 students as subjects and an instrument consisting of 20 multiple-choice items. Data were analyzed using the Anates application to determine item validity, discriminative power, difficulty level, distractor effectiveness, and test reliability. The analysis results indicate that the test instrument has high reliability at 0.87. Regarding validity, 9 items demonstrated good validity, 8 items were not yet significant, and 3 items could not have their correlation values calculated. In terms of discriminative power, several items effectively distinguished students’ abilities, particularly items 12, 15, 16, and 18, while others still require improvement. The difficulty levels of the items also varied, ranging from very difficult to very easy. Additionally, the quality of distractors in some items functioned well, but there were still some ineffective distractors. Thus, item analysis based on Anates can assist educators in assessing the quality of evaluation instruments and serve as a basis for improving test items to make them more valid, objective, and appropriate for students’ abilities.